Drag expressions to complete each equation.
![Drag expressions to complete each equation class=](https://us-static.z-dn.net/files/d1a/989136cf243b3a7b714d8fd3db7b831d.png)
[tex]a^{-b} =\frac{1}{a^{b}}[/tex]
[tex]\frac{a^{b}}{a^{c}} = a^{b-c}[/tex]
[tex]\frac{a^{c}}{b^{c}} =(\frac{a}{b} )^{c}[/tex]
When you have a negative exponent, you move the variable with the negative exponent to the opposite side of the fraction to make the exponent positive.
For example:
[tex]x^{-2} =\frac{1}{x^{2}}[/tex]
[tex]\frac{1}{x^{-2}} =\frac{x^{2}}{1}[/tex] or [tex]x^{2}[/tex]
When you have an exponent divided by an exponent, you subtract the exponents together.
For example:
[tex]\frac{x^5}{x^2} =x^{5-2} =x^3[/tex]
[tex]\frac{x^2}{x^1} = x^{2-1} = x^1[/tex]
When you multiply an exponent directly into a variable with an exponent, you multiply the exponents together.
For example:
[tex](x^{2} )^{4} = x^8[/tex]
[tex](\frac{x^2}{y^3} )^5=\frac{x^{10}}{y^{15}}[/tex]
[tex](\frac{x^1}{y^1} )^b = \frac{x^b}{y^b}[/tex]